γ-Linolenic Acid versus α-Lipoic Acid for Treating Painful Diabetic Neuropathy in Adults: A 12-Week, Double-Placebo, Randomized, Noninferiority Trial - Won, Jong Chul; Kwon, Hyuk-Sang; Moon, Seong-Su; Chun, Sung Wan; Kim, Chong Hwa; Park, Ie Byung; Kim, In Joo; Lee, Jihyun; Cha, Bong Yun; Park, Tae Sun (Diabetes & metabolism journal, 2020)
Background This study was a multicenter, parallel-group, double-blind, double-dummy, randomized, noninferiority trial to evaluate the efficacy and safety of γ-linolenic acid (GLA) relative to α-lipoic acid (ALA) over a 12-week treatment period in type 2 diabetes mellitus (T2DM) patients with painful diabetic peripheral neuropathy (DPN).* Methods This study included 100 T2DM patients between 20 and 75 years of age who had painful DPN and received either GLA (320 mg/day) and placebo or ALA (600 mg/day) and placebo for 12 weeks. The primary outcome measures were mean changes in pain intensities as measured by the visual analogue scale (VAS) and the total symptom scores (TSS).* Results Of the 100 subjects who initially participated in the study, 73 completed the 12-week treatment period. Per-protocol analyses revealed significant decreases in the mean VAS and TSS scores compared to baseline in both groups, but there were no significant differences between the groups. The treatment difference for the VAS (95% confidence interval [CI]) between the two groups was −0.65 (−1.526 to 0.213) and the upper bound of the 95% CI did not exceed the predefined noninferiority margin (δ1=0.51). For the TSS, the treatment difference was −0.05 (−1.211 to 1.101) but the upper bound of the 95% CI crossed the noninferiority margin (δ2=0.054). There were no serious adverse events associated with the treatments.* Conclusion GLA treatment in patients with painful DPN was noninferior to ALA in terms of reducing pain intensity measured by the VAS over 12 weeks.